Multiple secularities beyond the west : religion and modernity in the global age - Burchardt, Marian; Wohlrab-Sahr, Monika; Middell, Matthias (Boston : De Gruyter, 2015)
Questions of secularity and modernity have become globalized, but most studies still focus on the West. This volume breaks new ground by comparatively exploring developments in five areas of the world, some of which were hitherto situated at the margins of international scholarly discussions: Africa, the Arab World, East Asia, South Asia, and Central and Eastern Europe. It examines the historical pathways, cultural meanings, and global entanglements of secular formations.
Part 1. Religious communities and the state: fault-lines of religion and secularity in South Asia -- part 2. Nationalism, Islam and democratization: secular dynamics in the Arab world -- part 3. Secularities in East Asia -- part 4. African scenarios: (post- )colonial secularity vs. African religiosity? -- part 5. The sacred secular: secularities in post-Communist central and Eastern Europe -- Conclusions.
Includes bibliographical references and index.
Online resource; title from PDF title page (De Gruyter, viewed May 28, 2015).
Keywords: Religions; Secularism; Religions; Secularism; Religions; Secularism; RELIGION / Comparative Religion; RELIGION / Essays; RELIGION / Reference; Electronic books